Service quality (SERVQUAL) model in private higher education institutions: A bibliometric analysis of past, present, and future prospects - Wider, Walton; Tan, Foong Ping; Tan, Yen Ping; Lin, Jiaming; Muhammad Ashraf, Fauzi; Wong, Lingshing; Tanucan, Jem Cloyd M.; Hossain, Syed Far Abid (Elsevier Ltd, 2024)
The purpose of this study is to conduct a bibliometric analysis of Service Quality (SERVQUAL) research in private higher education institutions (HEIs). This analysis aims to provide a comprehensive evaluation of SERVQUAL's current state and future potential in private HEIs. This study collected 205 journal articles from the Web of Science database using a bibliometric approach. Then, co-citation and co-word analyses were conducted to determine the most influential publications, analyze the knowledge structure, and forecast future trends. This review offers valuable insight into the expanding field of SERVQUAL research, despite its limitations, as the analysis revealed five clusters in co-citation and co-word analysis, respectively. This study contributes to the existing body of knowledge by offering a comprehensive understanding of SERVQUAL in the context of private HEIs. Additionally, it provides insight into potential future developments in this field.